ANALYSIS OF THE INFLUENCE OF LEBAK BULUS TERMINAL EXPANSION TOWARD LAND USE IN THE ENVIRONMENT - Ariesta Kirana Sari, Dayu; Dayana Ekahanny, Dea; Fuji Widyawati, Laili; Andari, Diah (International Journal of Psychosocial Rehabilitation, 2020)
In the process of urban development, the terminal is one of the factors forming the structure of urban space that is important for changes in activity and land use around it. Infrastructure expansion influences the activities inside, the wider the infrastructure, the greater the impact on the surrounding environment. In 2012 the DKI Jakarta Government planned the construction of Jakarta Mass Rappid Transit (MRT) mass transportation, and the Lebak Bulus Terminal selected as one of the Jakarta MRT Station Depots. In the construction of the Jakarta MRT Station, the Lebak Bulus Terminal will be expanded to 12 Ha for the needs of facilities and infrastructure to support the Jakarta MRT Station. This study aims to see the effect of the expansion of the Lebak Bulus Terminal on the use of land in the surrounding environment. The method used in this research is Quantitative Descriptive Analysis using Geographical Information Systems, assisted by Arcgis 10.1. The results of this study are that the expansion of the Lebak Bulus Terminal for the Jakarta MRT Station requires additional area from the previous terminal area of 2.20 Ha to 12 Ha and requires the relocation of 103 buildings around the terminal to meet the needs of the terminal land for the construction of the Jakarta MRT Station. The expansion of the Lebak Bulus Terminal influences land use changes, especially in residential land use which decreased by 10% from 2010 to 2015 land use, trade and service land use increased by 2% from 2010 to 2015, and green space decreased by 4 % from 2010 to 2015.